Digitalisasi UMKM Bidang Kuliner terhadap Pertumbuhan Ekonomi - Alfin Agung Az’har; Zuhrinal M. Nawawi (Universitas Muhammadiyah Enrekang, 2022)
In this era of development, the engineering of ideas can start from a small place and then grow into a bigger one and become a company that affects millions of people around them. Culinary SMEs can now take advantage of the innovations provided by Gojek. Especially in the food delivery service, namely GoFood. Departing from that, Grab launched the GrabMerchant application which is specifically designed to help MSME owners (Micro, Small and Medium Enterprises) digitize their business. It is desirable that on this occasion the article is also designed as a learning material and informs that technological developments can digitize micro, small and medium enterprises for economic growth so that SMEs in the community can increase by using Grab and GojekGrab Indonesia with food. delivery service feature - GrabFood offers delivery services at quite competitive prices. The research explains that GrabFood merchant partners and GrabKios agents experienced a 35% and 17% increase in sales respectively after joining Grab, and 12% of GrabFood's merchant partners said they were inspired to start their business because of GrabFood. As the business of GrabKios merchant partners and agents grows, they also accept Grab workers from their community. Overall, the main benefits that SMEs feel from partnering with GoFood are GoFood promotion opportunities, expansion of market access, ease of operation through the GoBiz application, and entrepreneurship training. Moreover, 3 out of 4 partner MSMEs get GoFood commissions according to the profits received. On this occasion, the author of the article wants to introduce the digitization of micro, small and medium enterprises to technological developments by utilizing third parties, namely companies engaged in digital transportation services that have the convenience of developing micro, small and medium enterprises. companies with offers and policies that certainly increase economic growth, it is time for MSMEs to develop with digitalization in the 4.0 era which will soon reach 5.0